Country-by-country reporting and other financial transparency measures affecting the European Union - Petr Janský; Andres Knobel; Markus Meinzer; Tereza Palanská (Charles University in Prague, Institute of Economic Studies (IES), 2020)
In this paper we use the recently developed Bilateral Financial Secrecy Index to evaluate which countries supply most secrecy to EU Member States. Then, we assess how well-aimed are two of the EU's recent policy efforts to increase financial transparency: automatic Country-by-Country Reporting information exchange (CbCRIE) and the blacklist and the greylist of non-cooperative jurisdictions. We find that more than one-third of the financial secrecy that the EU faces comes from within the EU itself, and that the United States, Switzerland, and the Cayman Islands are the largest non-EU suppliers of secrecy to EU Member States. We report that active CbCRIE relationships now cover 79 per cent of the secrecy faced by the EU, but there is considerable heterogeneity in the share of secrecy that is covered by CbCRIE across the individual EU Member States, pointing to the potential to better aim the efforts of policymakers in identifying the most critical secrecy jurisdictions for individual countries. We further find that the blacklist and the greylist of noncooperative jurisdictions published by the European Commission overlap with our results for most of the critical jurisdictions, with the significant exception of the United States.
Keywords: F36; F63; F65; H26; O16; 330; tax havens; secrecy jurisdictions; financial secrecy; financial transparency; offshore finance; automatic exchange of information; European Union